2015
DOI: 10.17224/energagric.2015v30n4p418-428
|View full text |Cite
|
Sign up to set email alerts
|

Análise Energética Da Produção De Milho Para Silagem Cultivado Em Diferentes Espaçamentos

Abstract: Tendo em vista a crescente demanda por alimentos e uma agricultura cada vez mais desenvolvida, é importante avaliar os impactos causados pelos agroecossistemas no que se refere à sustentabilidade ambiental. Nesse contexto, o balanço energético constitui uma importante ferramenta para essa avaliação, pois permite contabilizar os "inputs" e "outputs" referentes ao sistema produtivo na forma de energia e determinar a eficiência de cada um. O presente trabalho teve como objetivo avaliar os fluxos de energia do pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 23 publications
0
9
1
3
Order By: Relevance
“…It was possible to observe a strong predominance of direct energy consumption (42,357.67 and 43,118.56MJ ha -1 ) in comparison to the indirect one (3,286.18 and 4,185.04MJ ha -1 ). Most of the authors that used a similar energy classification also reported a greater influence of direct energy in their energy matrix (ANGONESE et al, 2006;BIAGGIONI;BOVOLENTA, 2010;CUNHA et al, 2015;MARTINS et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was possible to observe a strong predominance of direct energy consumption (42,357.67 and 43,118.56MJ ha -1 ) in comparison to the indirect one (3,286.18 and 4,185.04MJ ha -1 ). Most of the authors that used a similar energy classification also reported a greater influence of direct energy in their energy matrix (ANGONESE et al, 2006;BIAGGIONI;BOVOLENTA, 2010;CUNHA et al, 2015;MARTINS et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The experimental area used 11 ha from the total 119.80ha of the CDDT-UFLA. The soil was classified as red-yellow latosol (RYL) of clayey texture and the climate of the region is considered as humid temperate with dry winter and hot summer (Cwa) according to the Köppen classification (MARTINS et al,2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations